Sound before meaning: word learning in autistic disorders. - Norbury, C; Griffiths, H; Nation, K (2010)
Successful word learning depends on the integration of phonological and semantic information with social cues provided by interlocutors. How then, do children with autism spectrum disorders (ASDs) learn new words when social impairments pervade? We recorded the eye-movements of verbally-able children with ASD and their typical peers while completing a word learning task in a social context. We assessed learning of semantic and phonological features immediately after learning and again four weeks later. Eye-movement data revealed that both groups could follow social cues, but that typically developing children were more sensitive to the social informativeness of gaze cues. In contrast, children with ASD were more successful than peers at mapping phonological forms to novel referents; however, this advantage was not maintained over time. Typical children showed clear consolidation of learning both semantic and phonological information, children with ASD did not. These results provide unique evidence of qualitative differences in word learning and consolidation and elucidate the different mechanisms underlying the unusual nature of autistic language.